Feature Selection to Enhance Phishing Website Detection Based On URL Using Machine Learning Techniques - Mat Rani, Liyana; Mohd Foozy, Cik Feresa; Mustafa, Siti Noor Baini (Journal of Soft Computing and Data Mining, 2023)
The detection of phishing websites based on machine learning has gained much attention due to its ability to detect newly generated phishing URLs. To detect phishing websites, most techniques combine URLs, web page content, and external features. However, the content of the web page and external features are time-consuming, require large computing power, and are not suitable for resource-constrained devices. To overcome this problem, this study applies feature selection techniques based on the URL to improve the detection process. The methodology for this study consists of seven stages, including data preparation, preprocessing, splitting the dataset into training and validation, feature selection, 10-fold cross-validation, validating the model, and finally performance evaluation. Two public datasets were used to validate the method. TreeSHAP and Information Gain were used to rank features and select the top 10, 15, and 20. These features are fed into three machine learning classifiers which are Naïve Bayes, Random Forest, and XGBoost. Their performance is evaluated based on accuracy, precision, and recall. As a result, the features ranked by TreeSHAP contributed most to improving detection accuracy. The highest accuracy of 98.59 percent was achieved by XGBoost for the first dataset with 15 features. For the second dataset, the highest accuracy is 90.21 percent using 20 features and Random Forest. As for Naïve Bayes, the highest accuracy recorded is 98.49 percent using the first dataset.